Al-Usthurah fi al-Qishah Al-Qur’aniyah ‘Inda Muhammad Ahmad Khalafullah - Asif Trisnani; Rofiidah Auliatur Rohmah (Universitas Darussalam Gontor, 2019)
This article examines the story on Qur'an which is one of the greatest elements in the Qur'an. It shows that a story has become an easy intermediary for delivering messages and lessons. Muhammad Ahmad Khalafullah is a contemporary Islamic intellectual Faculty of Art and Literatures, Cairo University, in 1939, offered his thoughts in his dissertation about reading Qur'anic story. It aimed to make the Qur'an reader and researchers are able to take full existence from stories in Qur'an. Through its comprehension of story style in Qur'an One of his seemingly contradictory thoughts is the existence of an element of mythology in the story of the Qur'an. The methodology in this discussion is the method of analysis of the thoughts of Muhammad Ahmad Khalafullah along with the criticisms with the foundations of the arguments and arguments of scientist Qur'an. it is understood that the story in the Qur'an Muhammad Khalafullah is an opinion that makes misunderstanding over the Qur'an itself.